Development and experimental study of a small-scale compressed air radial inflow turbine for distributed power generation. (April 2017) - Rahbar, Kiyarash; Mahmoud, Saad; Al-Dadah, Raya K.; Moazami, Nima; Mirhadizadeh, Seyed A.
Highlights: Proposing methodology for developing small-scale RIT as expander of CAES and ORC. 1D modelling enables estimation of turbine performance and obtaining key geometry. Turbine efficiency improved from 81.3% obtained by 1D model to 84.5% obtained by CFD. CFD predicts turbine efficiency and power with accuracy of ±16% and ±13% compared to tests. Abstract: With ever increasing demand on energy, disturbed power generation utilizing efficient technologies such as compressed air energy storage (CAES) and organic Rankine cycle (ORC) are receiving growing attention. Expander for such systems is a key component and its performance has substantial effects on overall system efficiency. This study addresses such component by proposing an effective and comprehensive methodology for developing a small-scale radial inflow turbine (RIT). The methodology consists of 1-D modelling, 3-D aerodynamic investigation and structural analysis, manufacturing with pioneering technique and experimental testing for validation. The proposed 1-D modelling was very effective in determining the primary geometry and performance of turbine based on parametric studies of turbine input design variables. However with CFD analysis, it was shown that more efficient turbine geometry can be achieved that not only provides more realistic turbine performance by capturing the 3-D fluid flow behaviour but also improves turbine efficiency with the aid of parametric studies of turbine geometry parameters. Turbine efficiency was improved from 81.3% obtained from 1-D modelling to 84.5% obtained by CFD. Accuracy of the CFD model was assessed by conducting experiments on the RIT manufactured with stereolithography technique. The CFD model can predict turbine efficiency and power with accuracy of ±16% and ±13% respectively for a wide range of tested operating conditions. Such results highlights the effectiveness of the proposed methodology and the CFD model can be used as benchmarking model for analyses of small-scale RITs. Besides, it was shown that for such applications, the novel manufacturing technique and employed material are very effective for producing prototypes that assist design decisions and validation of CFD model with reasonable accuracy at reasonable cost and in timely manner.